Establishment of a pig CRISPR/Cas9 knockout library for functional gene screening in pig cells. Issue 7 (10th November 2021) - Yu, Chuanzhao; Zhong, Haiwen; Yang, Xiaohui; Li, Guoling; Wu, Zhenfang; Yang, Huaqiang
Abstract: Background: As an important farm animal, pig functional genomic study can help understand the molecular mechanism related to the key economic traits of pig, such as growth, reproduction, or disease. The genome‐scale library based on clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR‐associated endonuclease Cas9 (Cas9) system facilitates discovery of key genes involved in a specific function or phenotype, allowing for an effective "phenotype‐to‐genotype" strategy for functional genomic study. Methods and Results: We designed and constructed a pig genome‐scale CRISPR/Cas9 knockout library targeting 16, 888 genes with 970, 001 unique sgRNAs. The library is a single‐vector system including both Cas9 and sgRNA, and packaged into lentivirus for an easy cell delivery for screening. To establish a screening method in pig cells, we used diphtheria toxin (DT)‐induced cell death as a model to screen the host genes critical for DT toxicity in pig PK‐15 cells. After lentiviral transduction and two sequential screening with DT treatment, the highest‐ranking candidates we identified were previously validated genes, HBEGF, DPH1, DPH2, DPH3, DPH5, DNAJC24, and ZBTB17, which are DT receptor and the key factors involved in biosynthesis of diphthamide, the target of DT action. The function and gene essentiality of candidates were further confirmed by gene knockout and DT toxicity assay in PK‐15 cells. Conclusions: Our CRISPR knockout library targeting pig whole genome establishes a promising platform for pig functional genomic analysis. Graphical Abstract and Lay Summary: A pig genome‐wide CRISPR knockout library harboring 970, 001 unique sgRNAs and targeting 16, 888 genes was constructed for pig genome screening to identify host genes associated with phenotype of interest. The authors established an effective workflow for CRISPR library screening using diphtheria toxin‐induced cell death model in pig cells. The reported CRISPR knockout library targeting pig whole genome establishes a promising platform for pig functional genomic analysis.